Effect of wall orientation on the optimum insulation thickness by using a dynamic method - Ozel, Meral (Elsevier Sci Ltd, 2011)
A comprehensive economic analysis has been performed to inter-relate the optimum thickness of insulation materials for various wall orientations. The yearly cooling and heating transmission loads of building walls were determined by use of implicit finite-difference method with regarding steady periodic conditions under the climatic conditions of Elazig, Turkey. The economic model including the cost of insulation material and the present value of energy consumption cost over lifetime of 10 years of the building was used to find out the optimum insulation thickness, energy savings and payback periods for all wall orientations. Considered insulation materials in the analysis were extruded polystyrene and polyurethane. As a result, the optimum insulation thickness of extruded polystyrene was found to be 5.5 cm for south oriented wall and 6 cm for north, east and west oriented walls. Additionally, the lowest value of the optimum insulation thickness and energy savings were obtained for the south oriented wall while payback period was almost same for all orientations. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Optimum insulation thickness; Dynamic thermal condition; Wall orientations; Energy savings